2015
DOI: 10.1007/s11832-015-0658-8
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of a physiotherapist-led Ponseti service for the management of non-idiopathic and idiopathic clubfoot

Abstract: Background The Ponseti method is the preferred treatment for idiopathic clubfoot. Although popularised by orthopaedic surgeons it has expanded to physiotherapists and other health practitioners. This study reviews the results of a physiotherapist-led Ponseti service for idiopathic and non-idiopathic clubfeet and compares these results with those reported by other groups. Method A prospective cohort of clubfeet (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) with a minimum 2-year follow-up after correction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…Like some recent studies [1][2][3][4][11][12][13][14], this study showed satisfactory results with nonidiopathic clubfeet treated by the Ponseti method as initial successful results 81.3%, early relapses 26.9%, and poor latest follow-up results 31.3%. However, the Ponseti method was less successful in the syndromic and neuromuscular patients when compared with the group of idiopathic clubfeet in this study (Table 2); these results were almost similar to the results of other studies over the same follow-up period despite there were different results of some variables in detail (Table 4).…”
Section: Discussionsupporting
confidence: 79%
“…Like some recent studies [1][2][3][4][11][12][13][14], this study showed satisfactory results with nonidiopathic clubfeet treated by the Ponseti method as initial successful results 81.3%, early relapses 26.9%, and poor latest follow-up results 31.3%. However, the Ponseti method was less successful in the syndromic and neuromuscular patients when compared with the group of idiopathic clubfeet in this study (Table 2); these results were almost similar to the results of other studies over the same follow-up period despite there were different results of some variables in detail (Table 4).…”
Section: Discussionsupporting
confidence: 79%
“…This is also concluded in a recent review article [ 8 ]. Traditionally the treatment is medical-led, but physiotherapist-led Ponseti clinics have shown equally good results, even in non-idiopathic and complex clubfeet [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 27 , 28 Defining non-compliance as use of brace less than ten hours per day before four years of age is a more strict definition. 4 , 29 It is our experience that children often partly comply with the brace and that is why we differentiated brace compliance. Overall brace compliance in our study was rather good as 61% of the children used the brace as prescribed for four years, and 20% were defined as poor or non-compliant.…”
Section: Discussionmentioning
confidence: 99%